2013
DOI: 10.3389/fnhum.2013.00898
|View full text |Cite
|
Sign up to set email alerts
|

Do neural correlates of face expertise vary with task demands? Event-related potential correlates of own- and other-race face inversion

Abstract: We are typically more accurate at remembering own- than other-race faces. This “own-race bias” has been suggested to result from enhanced expertise with and more efficient perceptual processing of own-race than other-race faces. In line with this idea, the N170, an event-related potential correlate of face perception, has been repeatedly found to be larger for other-race faces. Other studies, however, found no difference in N170 amplitude for faces from diverse ethnic groups. The present study tested whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 66 publications
(113 reference statements)
2
45
0
Order By: Relevance
“…While these studies show that expertise with a class of stimuli is a requirement for configural processing and the appearance of inversion effects, other studies have also shown that familiarity with specific exemplars within a class of stimuli boosts the use of configural processing (Buttle & Raymond, ; Marzi & Viggiano, ; Veres‐Injac & Persike, ), leading to an advantage for processing familiar versus unfamiliar faces that is lost when stimuli are inverted (Keyes, ). To a similar influence of familiarity are attributed the well‐known own‐race (Meissner & Brigham, ) and own‐age (Rhodes & Anastasi, ) effects, with better performance (Byatt & Rhodes, ; Fulton & Bartlett, ) and greater inversion effects (Rhodes et al., ; Stein et al., ; Wiese, ) for recognition of faces belonging to the same ethnic or age group of the observer or even to a different ethnic or age group with which the observer has had frequent contacts (Hancock & Rhodes, ; Proietti et al., ). While research on the effects of familiarity on body configural processing is less plentiful, a few recent studies have suggested larger inversion effects for familiar than unfamiliar body identities (Robbins & Coltheart, ) and for possible or typical (e.g., humanlike) than impossible or atypical (e.g., doglike) body postures (Reed, Nyberg, & Grubb, ; Reed et al., ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…While these studies show that expertise with a class of stimuli is a requirement for configural processing and the appearance of inversion effects, other studies have also shown that familiarity with specific exemplars within a class of stimuli boosts the use of configural processing (Buttle & Raymond, ; Marzi & Viggiano, ; Veres‐Injac & Persike, ), leading to an advantage for processing familiar versus unfamiliar faces that is lost when stimuli are inverted (Keyes, ). To a similar influence of familiarity are attributed the well‐known own‐race (Meissner & Brigham, ) and own‐age (Rhodes & Anastasi, ) effects, with better performance (Byatt & Rhodes, ; Fulton & Bartlett, ) and greater inversion effects (Rhodes et al., ; Stein et al., ; Wiese, ) for recognition of faces belonging to the same ethnic or age group of the observer or even to a different ethnic or age group with which the observer has had frequent contacts (Hancock & Rhodes, ; Proietti et al., ). While research on the effects of familiarity on body configural processing is less plentiful, a few recent studies have suggested larger inversion effects for familiar than unfamiliar body identities (Robbins & Coltheart, ) and for possible or typical (e.g., humanlike) than impossible or atypical (e.g., doglike) body postures (Reed, Nyberg, & Grubb, ; Reed et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, while evidence of inversion effects is strongly supported by previous studies for both faces (Maurer et al, 2002) and bodies (e.g., Reed et al, 2003Reed et al, , 2006Urgesi, Calvo-Merino, Haggard, & Aglioti, 2007), evidence of composite effects (and holistic processing) is consistent for faces (Maurer et al, 2002), but still controversial for bodies (Soria Bauser, Suchan, & Daum, 2011;Willems, Vrancken, Germeys, & Verfaillie, 2014). Importantly, the extension of configural processing use is dependent on the familiarity the observer has with the stimulus category and with specific exemplars within each category, being higher, for example, for familiar than unfamiliar faces (Buttle & Raymond, 2003;Keyes, 2012;Veres-Injac & Persike, 2009) and for faces belonging to the same ethnic (Rhodes, Tan, Brake, & Taylor, 1989;Wiese, 2013) or age (Proietti, Pisacane, & Macchi Cassia, 2013;Stein, End, & Sterzer, 2014) group of the observer. Nevertheless, whether and to which extent configural processing of faces and bodies is related to maternal sensitivity remain unknown.…”
mentioning
confidence: 99%
“…Previous ERP research on the own-race bias has identified a number of components that differentiate between the processing of own-and other-race faces. First, the N170, a negative deflection peaking approximately 170 ms after stimulus onset (Bentin, Allison, Puce, Perez, & McCarthy, 1996), has been repeatedly found to be larger for other-relative to ownrace faces (e.g., Caharel et al, 2011;Cassidy, Boutsen, Humphreys, & Quinn, 2014;Herrmann et al, 2007;Herzmann, 2016;Montalan et al, 2013;Stahl, Wiese, & Schweinberger, 2008Walker, Silvert, Hewstone, & Nobre, 2008;Wiese, 2012Wiese, , 2013Wiese, Kaufmann, & Schweinberger, 2014). The N170 is usually assumed to reflect processes prior to the identification of individual faces, such as the detection of a face-like stimulus or structural encoding (Amihai, Deouell, & Bentin, 2011;Eimer, 2011;Schweinberger & Burton, 2003).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…These behavioral effects are reflected in early ERP components associated with face perception. Face inversion causes an increased amplitude and/or increased peak latency in the P100 (Colombatto & McCarthy, 2016;Feng, Martinez, Pitts, Luo, & Hillyard, 2012;Itier & Taylor, 2002, 2004a, 2004b and N170 (Bentin, Allison, Puce, Perez, & McCarthy, 1996;Eimer 2000;Itier & Taylor, 2004c;Rossion et al, 1999Rossion et al, , 2000Wiese 2013).…”
Section: Introductionmentioning
confidence: 99%